5PSQ-077 Are patients satisfied with their biological treatment?. (2nd March 2018) - Retamero, A; Grados, MD; Cucurell, M; Colquechambi, AM; Bové, J; Sanchez, S; Salom, C; Sanchez, X; Parés, RM; Serrais, J; Ferràndez, D
Abstract : Background: According to recent literature, satisfaction with biologic treatment (BT) is quite high despite the risk of adverse events. 1, 2 Purpose: To determine the degree of satisfaction among patients with rheumatologic and dermatological diseases treated with BT in our reference area. Material and methods: Prospective study conducted during 3 months in a regional hospital with 180 BT. A survey was conducted to all patients who collected their medication at the pharmacy service and those whose treatment was administered by the nursing staff. Satisfaction degree before and after the BT and improvement of pain was evaluated from 0 to 10. Statistical analysis was carried out with SPSS Statistics v.22. Results were presented with mean and standard deviation for quantitative data and percentage for qualitative data. All patients received an information sheet and signed an informed consent form. Results: Finally, 111 patients answered the survey (response rate: 61.7%): 51 (45.9%) males, age 53 (14.3). Forty-nine (44.1%) patients were actively employed. Distribution by pathologies: 49 (44.2%) rheumatoid arthritis, 34 (30.6%) psoriasis, 18 (16.2%) psoriatic arthritis, seven (6.3%) spondyloarthropathies, two (1.8%) suppurative hydrosadenitis and one (0.9%) juvenile idiopathic arthritis. Distribution of BT: 49 (44.2%) adalimumab, 28 (25.2%) ustekinumab, 18 (16.2%) etanercept, three (2.7%) golimumab, six (5.4%) tocilizumab, six (5.4%) secukinumab, one (0.9%) abatacept. Treatment was self-administered in 65 (58.6%) patients. Only 39 (35.1%) patients had undergone previous BT. At present, 38 (34.2%) patients had some additional treatment, 34 with methotrexate and four with leflunomide. Table 1 shows the results of the survey: Conclusion: In line with recent publications, satisfaction degree of patients with BT in our reference area is very high. Most of them are in monotherapy. Sixty-five patients are comfortable with the route of administration and self-administered the drug at home. Nearly 94% of patients consider that there has been an improvement in their quality of life. References and/or Acknowledgements: 1. Patient Prefer Adherence2017Jul 19;11:1243–1252. 2. Br J Dermatol2014Mar;170(3):672–680. No conflict of interest